GAMBARAN PENGETAHUAN PERILAKU CERDIK UPAYA PREVENTIF PENYAKIT DEGENERATIF PADA REMAJA - Lautan, Lydia Moji; Ardhana, Putra; Amanda, Antonia Sovia (Jurnal Keperawatan dan Kesehatan, 2025)
Introduction: Degenerative diseases are a group of non-communicable diseases that occur due to damage or a gradual decline in the function of body tissues and organs. These diseases are often associated with the aging process and lifestyle. Currently, degenerative diseases are one of the increasing health problems in Indonesia, affecting not only the elderly, but also adolescents. The underlying risk factors for the occurrence of degenerative diseases include unhealthy lifestyles such as lack of physical activity, poor diet, exposure to cigarette smoke, stress, and lack of health checks. Therefore, early prevention efforts can be carried out through the CERDIK behavior movement (Regular health checks, Eliminate cigarette smoke, Regular physical activity, Balanced diet, Adequate rest, and Stress management) which is one of the programs of prevention and control of non-communicable diseases of the Ministry of Health since 2012. This study aims to determine the overview of adolescents' knowledge regarding CERDIK behavior in preventing degenerative diseases. The research method in this study used a quantitative descriptive design with a survey approach. The study sample consisted of 40 people, data were collected through pre-test and post-test questionnaires, which were then analyzed using frequency distribution. The results of the study showed that adolescents' knowledge before the educational intervention was still relatively low. After being provided with health education, there was an increase in all CERDIK components, especially in the components of a balanced diet, eliminating cigarette smoke, and managing stress, although understanding of diligent physical activity was still low. The conclusion in this study shows that providing CERDIK-based health education has been proven to increase adolescents' knowledge regarding the prevention of degenerative diseases. This increase in knowledge is expected to encourage adolescents to adopt a healthy lifestyle from an early age